Biomarkers in WNT1 and PLS3 Osteoporosis: Altered Concentrations of DKK1 and FGF23. (11th February 2020) - Mäkitie, Riikka E; Kämpe, Anders; Costantini, Alice; Alm, Jessica J; Magnusson, Per; Mäkitie, Outi
ABSTRACT: Recent advancements in genetic research have uncovered new forms of monogenic osteoporosis, expanding our understanding of the molecular pathways regulating bone health. Despite active research, knowledge on the pathomechanisms, disease‐specific biomarkers, and optimal treatment in these disorders is still limited. Mutations in WNT1, encoding a WNT/β‐catenin pathway ligand WNT1, and PLS3, encoding X chromosomally inherited plastin 3 (PLS3), both result in early‐onset osteoporosis with prevalent fractures and disrupted bone metabolism. However, despite marked skeletal pathology, conventional bone markers are usually normal in both diseases. Our study aimed to identify novel bone markers in PLS3 and WNT1 osteoporosis that could offer diagnostic potential and shed light on the mechanisms behind these skeletal pathologies. We measured several parameters of bone metabolism, including serum dickkopf‐1 (DKK1), sclerostin, and intact and C‐terminal fibroblast growth factor 23 (FGF23) concentrations in 17 WNT1 and 14 PLS3 mutation‐positive subjects. Findings were compared with 34 healthy mutation‐negative subjects from the same families. Results confirmed normal concentrations of conventional metabolic bone markers in both groups. DKK1 concentrations were significantly elevated in PLS3 mutation‐positive subjects compared with WNT1 mutation‐positive subjects ( p < .001) or the mutation‐negative subjects ( p = .002). Similar differences were not seen in WNT1 subjects. Sclerostin concentrations did not differ between any groups. Both intact and C‐terminal FGF23 were significantly elevated in WNT1 mutation‐positive subjects ( p = .039 and p = .027, respectively) and normal in PLS3 subjects. Our results indicate a link between PLS3 and DKK1 and WNT1 and FGF23 in bone metabolism. The normal sclerostin and DKK1 levels in patients with impaired WNT signaling suggest another parallel regulatory mechanism. These findings provide novel information on the molecular networks in bone. Extended studies are needed to investigate whether these biomarkers offer diagnostic value or potential as treatment targets in osteoporosis. © 2020 American Society for Bone and Mineral Research.